Perubahan Kadar Estradiol dan Histologi Uterus Mencit (Mus musculus) Betina dengan Induksi Progesteron Sintetik - Erlia Narulita; Jekti Prihatin; Khoirul Anam; Fikri Ainur Risma Hardiyanti Oktavia (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
The purpose of this research was to determine the effect of progesterone to estradiol levels and histology of uterus, to test the effect of estrous cycle to uterus histology of females’ mice after treated by progesterone in birth control pills. This research used Completely Randomized Design (CRD). Females Mus musculus Balb-C and synthetic progesterone (cyproterone acetate) contained in ‘Diane-35’ birth control pills were used in this study. The research consisted of two treatment groups, i.e. group K had no treatment and group P treated by a solution of Diane-35 at a dose of 2.6 mg per 5 mL distilled water. Results on the effects of progesterone on endometrial thickness suggested that there were significant differences between treatment groups. Meanwhile, the effect of progesterone on estradiol levels indicated that there were no significant differences among treatment groups. This means that the thickness of the endometrium was strongly influenced by the presence of a synthetic progesterone hormone and induced endometrium growth thicker. The levels of estradiol are not significantly different due to a negative feedback mechanism of Follicle Stimulating Hormone (estrogen effect) and Luteinizing Hormone (progesterone effect). The greatest thickness of endometrium of estrous cycle was treated by progesterone, which was 0.2500 mm2.